Utilization of Ca2+-induced setting of alginate or low methoxyl pectin for noodle production from Japonica rice. (November 2018) - Nitta, Yoko; Yoshimura, Yukihiro; Ganeko, Natsuki; Ito, Hideyuki; Okushima, Nobuyuki; Kitagawa, Masaaki; Nishinari, Katsuyoshi
Abstract: Japonica rice is not generally appropriate for noodle production because of its stickiness and lack of firmness. In the present study, effects of Ca 2+ -induced setting of alginate or low methoxyl (LM) pectin on the firmness and stickiness of Japonica rice noodles were investigated. The Japonica rice noodles containing alginate or LM pectin showed a sufficient firmness after immersion in calcium chloride solutions judging from a peak force during compression. The firmness indexed by the peak force in the compression test could be increased ten/several times with increasing concentration of alginate/LM pectin and immersion time. Without Ca 2+ treatment the noodles did not show a clear peak force but just showed a gradual rise in the compression force. The surface stickiness of the noodles was evaluated by the adhesiveness of the newly introduced instrumental method. The adhesiveness of the noodles decreased with increasing alginate or LM pectin concentrations which should lead to a more slippery sensation. Thus the treatment of Ca 2+ -induced setting of alginate or LM pectin is promising for the gluten–free noodle production from Japonica rice. Highlights: Addition of alginate or pectin with calcium ions improves the texture of rice noodles. Stickiness of the noodle evaluated instrumentally could be reduced by alginate/pectin. Firmness of the noodle evaluated by the peak force in compression test could be increased.